The bled ones:: Biopolitical framings and scenes of interpellation in photographs from the Rockefeller Collection (Intercom - Brazilian Journal of Communication Sciences, 2026)
The article examines photographs produced by the Rockefeller Foundationduring health campaigns in Brazil (1930s–1940s), focusing on images of the“bled ones.” This qualitative, archival study identifies them not merely astechnical records but as scenes of interpellation that reveal agency, astutenessand self-fashioning of those portrayed. The methodology combines socialhistory, visual analysis, and theoretical approaches from Judith Butler,Saidiya Hartman, Tina Campt, and Jacques Rancière. The discussionshows how these images, although inscribed in a biopolitical logic, displayresistances and gestures that escape sanitary control. Results indicate thatsuch photographs establish alternative scenes of appearance, enablingcritical readings of the relationship between power, body, and visuality. Theconclusion is that, even under coercion, subjectivities emerge that displacethe exemplary function of the archive and open gaps for fabulations andalternative histories of epidemics.